Daily Monitoring of Soil Moisture in Thailand by FY-2E Satellite - Veerakachen, Watcharee; Raksapatcharawong, Mongkol (Agriculture and Natural Resources, 2014)
Soil moisture is an important factor in monitoring and warning of drought and landslide disasters. Direct observations of soil moisture are point-based which restricts measuring soil moisture across a wide area continuously. In Thailand, soil moisture measurements are also observed only for a specific purpose. A method for soil moisture estimation throughout the country does not exist due to the same limitation. Recent advanced technology in satellite remote sensing provides alternatives to indirectly estimate soil moisture with high temporal and spatial resolutions. This study presents an efficient technique to observe daily soil moisture based on apparent thermal inertia derived from FY-2E satellite data. The technique can estimate daily soil moisture throughout Thailand at 5 × 5 km pixel resolution. The results exhibited good consistency between observed daily soil moisture and other relevant factors, for example, diurnal temperature change and daily rainfall. This work suggests that the proposed technique is a feasible solution for daily soil moisture monitoring nationwide.